The Implementation English Songs on Listening Skills: English - Albadri Albadri; Lulu’ Diana (JOEY: Journal of English Ibrahimy, 2024)
This research aimed to know impelemantion of English song on listening skills in language room Ma’had Aly at Islamic boarding house of Salafiyah Syafi'iyah Sukorejo Situbondo”. The researcher used qualitative method. This research uses data collection methods. The aim of this research were to know about both teacher and students perception through English song on skill of listening. The topic of this study was speaking teacher and students’ at the first level in language room Ma’had Aly at the Islamic Boarding House of Salafiyah Syafi’iyah Sukorejo Situbondo. The results of this study demonstrated how learning and instruction through board games might improve speaking abilities and teachers' perceptions of, and students’ perception. Many students who took part in a teacher-student interview indicated that they had favorable opinions about the through English song on listening skill they were being happy, more spirit/enthusiastic, easier to understand, and improving their speaking skill, whereas there was also the negative perception such as: students feel difficult when the pronunciation was unclear.